1995
DOI: 10.1007/bf03028265
|View full text |Cite
|
Sign up to set email alerts
|

The laryngeal mask airway in obstetrical anaesthesia

Abstract: The laryngeal mask airway (LMA) has been used extensively to provide a safe airway in spontaneously breathing patients who are not at risk from aspiration of gastric contents. The role of the LMA in the event of a failed intubation in an obstetrical patient, and its place in a failed intubation drill remains unclear. Two hundred and fifty consultant obstetric anaesthetists in the United Kingdom were asked to complete an anonymous questionnaire regarding their views about using the laryngeal mask airway (LMA) i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1999
1999
2010
2010

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…2 9 Gature et al 5 reported the successful use of the LMA in 21/24 patients for failed intubation in obstetrics. In some of these patients the LMA was used as an airway intubator.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…2 9 Gature et al 5 reported the successful use of the LMA in 21/24 patients for failed intubation in obstetrics. In some of these patients the LMA was used as an airway intubator.…”
Section: Discussionmentioning
confidence: 99%
“…3 The current standard of practice for airway management of patients undergoing Cesarean section is to perform a rapid sequence induction followed by laryngoscope-guided tracheal intubation to protect the airway and facilitate ventilation. 4 The use of the LMA for Cesarean section has been limited to failed 5 or awake intubation 6 because of the perceived risk of aspiration and/or the need for positive pressure ventilation in the presence of high intraabdominal pressure. However, the risk of aspiration without tracheal intubation may have been overestimated in the obstetric population.…”
Section: Résultats : La Libération Des Voies Aériennes a éTé Efficacementioning
confidence: 99%
See 1 more Smart Citation
“…Case reports have described the successful use of the LMA and ILMA in the failed obstetric intubation with cannot intubate, cannot ventilate situation [60][61][62][63][64]. In a survey of obstetric anesthesia consultants in the United Kingdom, 72% of the respondents stated that they would use the LMA in the cannot intubate, cannot ventilate obstetric airway, and the survey suggested that the LMA was available in 91% of obstetric units [65]. Twenty four (of 250) consultant anesthetists had personal experience with the use of the LMA in obstetric anesthesia.…”
Section: Urgent Deliverymentioning
confidence: 94%
“…In a survey in the United Kingdom, 71.8% of obstetrical anesthesiologists advocated use of LMA in a CVCI situation. Eight anesthesiologists stated that LMA proved to be a 'lifesaver' (69). Recently, 18 obstetrics units in Ireland were surveyed for difficult airway equipment.…”
Section: Management Of Difficult Airway In Obstetricsmentioning
confidence: 99%